Endometrial echo patterns of embryo transfer day affect pregnancy outcomes in frozen embryo transfer cycles: a retrospective clinical study - Xi Cheng; Bin Yang; Li Wang; Jinzhao Ma; Xuan Huang; Kadiliya Jueraitetibaike; Cheng Zhou; Xu Tang; Haiyan Fu; Biying Li; Xiting Cai; Bing Yao; et al. (BMC Pregnancy and Childbirth)
Abstract Background The echo pattern constitutes an ultrasonic index that reflects the characteristics of the endometrium across various phases of the menstrual cycle. However, consensus of endometrial echo pattern and pregnancy outcomes is lacking in clinical application. Methods The retrospective cohort study analyzed the data from the electronic records of women who underwent frozen embryo transfer (FET) with hormone replacement treatment (not only one cycle per patient) between July 2020 to August 2021 at Reproduction Medicine Center of Jbnminling Hospital of Medical College of Nanjing University. A total of 138 cleavage stage embryo transfer cycles and 561 blastocyst transfer cycles were analyzed in this study. Transvaginal ultrasound scans were performed on the embryo transfer day. The endometrial echo pattern was classified into four types: A, B, B-C and C. Pattern A was defined as trilinear type, Pattern B, B-C and C were defined as non-trilinear type. All scans were conducted by experienced clinicians, and the images were reviewed by the same two physicians. The outcomes measured included embryo implantation rate, clinical pregnancy rate, first trimester abortion rate, and live birth rate. For the data that conforms to a normal distribution, two independent sample t-tests are used for comparison between two groups, and one-way analysis of variance (ANOVA) is used for comparison among multiple groups. For the data that does not conform to a normal distribution, rank sum tests (Kruskal-Wallis test) are used for inter-group comparisons. Count data are analyzed using chi-square tests. Logistic regression models were applied for the analysis of clinical outcome. Results The embryo implantation rate (p = 0.066), clinical pregnancy rate (p = 0.140), early abortion rate (p = 0.515) and live birth rate (p = 0.578) were similar between the 4 type of endometrial pattern groups in cleavage-stage embryo FET cycles. In blastocyst cycles, the implantation rate (p = 0.201) and clinical pregnancy rate (p = 0.555) did not differ between the four endometrial patterns. Patients with a Pattern A endometrium on blastocyst transfer day experienced a decreased live birth rate (19.05%) compared with Pattern B, Pattern B-C and Pattern C (p = 0.006. p = 0.008, p = 0.031 for Pattern A vs. Pattern B, Pattern A vs. Pattern B-C, Pattern A vs. Pattern C). The first trimester abortion rate of Pattern A is up to 40.00%, although there was no statistical difference (p = 0.118). In the cycles of non-trilinear type group, the early miscarriage rate (0.248 [95% CI, 0.067–0.914]; p = 0.036) was lower and the live birth rate (0.269 [95% CI, 0.089–0.810]; p = 0.020) was higher than trilinear type group. Conclusions Our retrospective study suggests that a trilinear pattern endometrium on blastocyst transfer was associated with a higher first trimester abortion rate and lower live birth rate.